Combined Liver and Kidney Transplant in a Patient with Budd-Chiari Syndrome Secondary to Autosomal Dominant Polycystic Kidney Disease Associated with Polycystic Liver Disease: Report of a Case with a 9-Year Follow-Up - Patricia Ramírez de la Piscina; Ileana Duca; Silvia Estrada; Rosario Calderón; Idoia Ganchegui; Amaia Campos; Katerina Spicakova; Leire Urtasun; Marta Salvador; Elvira Delgado; Raquel Bengoa; Francisco García-Campos (Case Reports in Gastrointestinal Medicine)
Polycystic liver disease (PLD) is a hereditary disease inherited by autosomal dominant trait that occurs as a frequent extrarenal manifestation of autosomal dominant polycystic kidney disease (ADPKD). We report a case of a 59-year-old woman diagnosed with ADPKD associated with PLD. End-stage chronic renal failure with a secondary Budd-Chiari syndrome developed during the patient’s clinical course. She underwent combined liver and kidney transplantation, with a successful response over a 9-year follow-up period.